Pengaruh Hughes Terhadap Perkembangan Identitas Kulit Hitam Melalui Karya Sastra Setelah Gerakan New-Negro Movement - Yusuf, Muhammad (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2024)
This article analyzes how Langston Hughes significantly impacted the development of African American literature during the Harlem Renaissance. Hughes, as one of the centers of the New Negro movement, fought for their freedom through his work in literature. The author adopts a socio-historical approach along with African American literary criticism to review the events that took place during the 1920s. The author discusses how Hughes enlightened other Black African-American writers, such as Maya Angelou and Amiri Baraka, to express freedom through their literary works. The writer found that Hughes inspired them by using everyday language and incorporating elements of blues and jazz into his work, making it accessible to the public.